A survey on Canadian pediatric hospital clinical/medical teaching unit implementation during the first and second wave of the COVID-19 pandemic - Kara K. Tsang (BMC, 2021)
Abstract Background As the COVID-19 pandemic heightened, infection control and prevention experts recommended clinical training opportunities be modified or discontinued, substantially impacting the function of clinical or medical teaching units (CTU). A CTU is structured to involve medical learners such that they become active participants of the health care team. Since a review of the literature demonstrates a paucity of data to guide pediatric CTU implementation during pandemic phases, we developed and disseminated a survey to assess Canadian practices. Method A group of infectious disease specialists and pediatric hospitalists developed, tested, and disseminated surveys to understand CTU clinical rounding and teaching practices during the waves of the COVID-19 pandemic. Result Our surveys demonstrate the variability in adapting rounding practices during this pandemic and highlights the opportunities to share our approaches and lessons learned to optimize learner experience and patient centered care during unprecedented times in our academic hospitals. We also show the pragmatic implementation of our new pediatric hospital CTU process that was informed by our survey results. Conclusion Our study demonstrates the variability in adapting rounding practices during this pandemic and highlights the opportunities to share our approaches and lessons learned to optimize learner experience and patient centered care during unprecedented times in our academic hospitals.